Dopamine and Dopamine Receptors in Alzheimer's Disease: A Systematic Review and Network Meta-Analysis - Pan, Xiongfeng; Kaminga, Atipatsa C.; Wen, Shi Wu; Wu, Xinyin; Acheampong, Kwabena; Liu, Aizhong (Frontiers in Aging Neuroscience, 2019)
Objective: The aim of this review was to synthesize, using random-effects model of meta-analysis, the link between dopaminergic system and Alzheimer’s disease. Methods: A detailed analysis protocol was registered at the PROSPERO database prior to data extraction (CRD42018110798). Electronic databases of PubMed, Embase, Web of Science, and Psyc-ARTICLES were searched up to December 2018 for studies that examined dopamine and dopamine receptors in relation to Alzheimer’s disease. Standardized mean differences (SMD) were calculated to assess group differences in the levels of dopaminergic neurometabolites. Results: Seventeen studies met the eligibility criteria. Collectively, they included 512 patients and 500 healthy controls. There were significantly lower levels of dopamine in patients with Alzheimer’s disease compared with controls (SMD= -1.56, 95% CI: -2.64 to -0.49). In addition, dopamine 1 receptor (SMD=-5.05, 95% CI: -6.14 to -3.97) and dopamine 2 receptor (SMD=-1.13, 95% CI: -1.52 to -0.74) levels were decreased in patients with Alzheimer’s disease compared with controls. The results of network meta-analysis indicated that the rank of correlation with Alzheimer’s disease from highest to lowest was dopamine (0.74), dopamine 2 receptor (0.49), dopamine 3 receptor (0.46), dopamine 4 receptor (0.33), dopamine 5 receptor (0.31), and dopamine 1 receptor (0.64). Conclusions: Overall, decreased levels of dopaminergic neurotransmitters were linked with the pathophysiology of Alzheimer’s disease. Nonetheless, there is a clear need for more prospective studies to validate these hypotheses.